Influence of psychological factors on pregnancy, childbirth and puerperium. A longitudinal study - Dolores Marín Morales; Mª Ángeles Bullones Rodríguez; Francisco Javier Carmona Monge; Mª Isabel Carretero Abellán; Mª Amparo Moreno Moure; Cecilia Peñacoba Puente (Fundación para el Desarrollo de la Enfermería, 2008)
The aim of the present study is to analyze different psychological factors (personality, psychiatric symptoms, pregnancy worries, beliefs about delivery, locus of control, coping styles) and its relation to clinical symptomatology and the presence of complications during pregnancy, quality of life indicators, perception and coping with labour pain, type of delivery, neonatal well-being indicators, delivery satisfaction, maternal bond development and care of the baby and presence of post-partum depression.To achieve this we will develop a prospective correlational longitudinal study. The sample will be composed by pregnant women from the area 9 from the Madrid Community that voluntarily accept the inclusion in this research.Structured questionnaires will be used to evaluate all the psychological variables in the following moments in time:- during the first and third trimester the following variables will be assessed: personality, psychiatric symptoms, pregnancy worries, delivery beliefs, locus of control, coping styles, first trimester physical sintomatology, quality of life indicators,- during the inmediate post-partum: pain during labour and after delivery, childbirth satisfaction,- during the puerperium: post-partum depression and anxiety, post-traumatic stress disorder, child bond, neonatal care, personality, psychiatric symptomatology.From the clinical record the following data will be obtained: sociodemographic variables, and parameters related to pregnancy evolution, delivery and puerperium that are relevant to the research.